Paint the town red - Lim, Anne-Marie Sian Ping (2016)
This paper presents Paint the Town Red (PTTR), the first youth-initiated integrated communication campaign in Singapore that aims to raise awareness and reduce stigma about HIV among youths, organised by four final year students from the Wee Kim Wee School of Communication and Information.